Study of the content of carbonic acids in the herbs of Сapsella bursa-pastoris (L.) Medik - H. P. Smoilovska; O. O. Maliuhina; O. К. Yerenko; T. V. Khortetska (The State Expert Center of the Ministry of Health of Ukraine, 2022)
Carboxylic acids are key compounds that play an important role in metabolism. They activate the endocrine glands, affect human immune status, have antioxidant, antimicrobial and anti-inflammatory effects. Plants rich in carboxylic acids are recommended for the prevention of various diseases. A promising source of biologically active substances are Capsella bursa-pastoris, which has a significant content of vitamins, flavonoids, organic, hydroxycinnamic, fatty acids, macro-and micronutrients, tannins. Capsella bursa-pastoris is known for such healing properties as wound healing, antimicrobial, antibacterial, antitumor, anti-inflammatory, antioxidant, antihypertensive, hepatoprotective. The plant material of Capsella bursa-pastoris has a hemostatic effect and stimulates the contractile activity of the uterus. The aim of the study was to study the qualitative composition and quantitative content of carboxylic acids in the herb of Capsella bursa-pastoris (L.) Medik. by chromato-mass spectrometry. For the study, we used the herb of Capsella bursa-pastoris (L.) Medik., which was collected during flowering period. Qualitative analysis of the content of organic acids was carried out by thin layer chromatography. Identification and quantitative content of carboxylic acids were performed by chromato-mass spectrometry on an Agilent Technology 6890N chromatograph with a mass spectrometric detector 5973N. 33 carboxylic acids were identified in the herb of Capsella bursa-pastoris - 14 organic and 19 fatty acids. The total content of organic acids is 8 041.60 ± 84.00 mg/kg with a predominance of aliphatic acids (citric, malic, fumaric and succinic). The fatty acid complex of the Capsella bursa-pastoris herb is represented by 11 saturated and 9 unsaturated fatty acids. The content of total fatty acids was 21 161.90 ± 256.45 mg/kg, of which the proportion of unsaturated acids is significantly higher than saturated. Linolenic, linoleic, palmitic acidsare dominant. The obtained resultsmake it possible to predict the antioxidant and anti-inflammatory activity of herbal medicines based on the raw materials of Capsella bursa-pastoris.